Wealth inequality, intergenerational transfers, and family background - Palomino, JC; Marrero, GA; Nolan, B; Rodríguez, JG (2021)
We estimate the contribution of intergenerational transfers (inheritances and gifts) and family background to wealth inequality in four OECD countries: France, Spain, Great Britain, and the USA. We compare the observed wealth distribution with a non-parametric counterfactual distribution where all differences in wealth associated with intergenerational transfers and family background are removed. Despite the diversity of the countries analysed, we find similar patterns. The combined contribution of intergenerational transfers and family background to wealth inequality is sizeable in the four countries, ranging from 36% in Great Britain to 49% in the USA. When interactions between the two factors are accounted for, and the Shapley value decomposition is used to fully disentangle the contribution of each factor based on its marginal contribution, intergenerational transfers account for between 26% in Great Britain and 36% of wealth inequality in France, with family background ranging from 9% in France to 17% in the USA.